Schisandrin B attenuates bleomycin-induced pulmonary fibrosis in mice through AKT-mTOR pathway - Zhou , Dengfeng; Hu, Jianwu; Yang, David H; Cai, Yuanping; Lu, Qiaofa (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Purpose: Schisandrin B (Sch B) is an active monomer of Schisandrin with anti-fibrosis pharmacological action. The study investigated whether Sch B alleviate bleomycin-induced (BLM-Induced) pulmonary fibrosis in mice and attempted to clarify its anti-fibrosis mechanism. Methods: Histopathological examination was performed by H&E staining and immunohistochemistry. The inflammatory cytokines and oxidative stress were determined by ELISA. Western blotting and immunofluorescence were used to investigate the possible molecular mechanism to attenuate pulmonary fibrosis by Sch B. Results: The results indicated that Sch B can significantly attenuate BLM-Induced pulmonary fibrosis, myofibroblast activation, and collagen fibers deposition in mice. In addition, Sch B can inhibit inflammatory response and oxidative stress in early stage. Furthermore, Sch B can inhibit pulmonary fibrosis by promoting autophagy via promoting the dephosphorylation of AKT-mTOR pathway. Conclusions: The results suggest that the anti-fibrotic effect of Sch B is potentially related to the activation of autophagy through AKT-mTOR pathway, and Sch B is a potential agent for the treatment of idiopathic pulmonary fibrosis.